The Southern Glacial Maximum 65, 000 years ago and its Unfinished Termination. (15th April 2015) - Schaefer, Joerg M.; Putnam, Aaron E.; Denton, George H.; Kaplan, Michael R.; Birkel, Sean; Doughty, Alice M.; Kelley, Sam; Barrell, David J.A.; Finkel, Robert C.; Winckler, Gisela; Anderson, Robert F.; Ninneman, Ulysses S.; et al.
Abstract: Glacial maxima and their terminations provide key insights into inter-hemispheric climate dynamics and the coupling of atmosphere, surface and deep ocean, hydrology, and cryosphere, which is fundamental for evaluating the robustness of earth's climate in view of ongoing climate change. The Last Glacial Maximum (LGM, ∼26–19 ka ago) is widely seen as the global cold peak during the last glacial cycle, and its transition to the Holocene interglacial, dubbed 'Termination 1 (T1)', as the most dramatic climate reorganization during this interval. Climate records show that over the last 800 ka, ice ages peaked and terminated on average every 100 ka ('100 ka world'). However, the mechanisms pacing glacial–interglacial transitions remain controversial and in particular the hemispheric manifestations and underlying orbital to regional driving forces of glacial maxima and subsequent terminations remain poorly understood. Here we show evidence for a full glacial maximum in the Southern Hemisphere 65.1 ± 2.7 ka ago and its 'Unfinished Termination'. Our 10 Be chronology combined with a model simulation demonstrates that New Zealand's glaciers reached their maximum position of the last glacial cycle during Marine Isotope Stage-4 (MIS-4). Southern ocean and greenhouse gas records indicate coeval peak glacial conditions, making the case for the Southern Glacial Maximum about halfway through the last glacial cycle and only 15 ka after the last warm period (MIS-5a). We present the hypothesis that subsequently, driven by boreal summer insolation forcing, a termination began but remained unfinished, possibly because the northern ice sheets were only moderately large and could not supply enough meltwater to the North Atlantic through Heinrich Stadial 6 to drive a full termination. Yet the Unfinished Termination left behind substantial ice on the northern continents (about 50% of the full LGM ice volume) and after another 45 ka of cooling and ice sheet growth the earth was at inter-hemispheric Last Glacial Maximum configuration, when similar orbital forcing hit maximum-size northern ice sheets and ushered in T1 and thus the ongoing interglacial. This argument highlights the critical role of full glacial conditions in both hemispheres for terminations and implies that the Southern Hemisphere climate could transition from interglacial to full glacial conditions in about 15, 000 years, while the Northern Hemisphere and its continental ice-sheets required half a glacial cycle. Highlights: Our 10 Be chronology shows that New Zealand's glaciers were in full-glacial position 65 ka ago. We make the case for a Southern Glacial Maximum 65 ka ago during MIS-4. Northern Ice Sheets were only about 80% of their LGM size during MIS-4. Therefore the transition of the Southern Glacial Maximum to warmer MIS-3 conditions remained an unfinished termination. Maximum size Northern Ice Sheets were critical for terminations of ice ages.